Review in The Management of Post-Craniotomy Pain - Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2019)
Pain can lead to increase in the sympathetic stimulation and thereby cause hypertension and rebleed in the operative site. The ideal management of pain in these circumstances is a topic of debate worldwide. The standard algorithm for pain management is usually with nonsteroidal anti-infl ammatory drugs (NSAIDS) with or without opioids. Good pain management helps to reduce not only the pain but also shortens hospital stay and cost and leads to early recovery but overenthusiastic use of drugs can lead to sedation, mydriasis, respiratory depression which could increase the intracranial pressure or obtundation of deteriorating neurological signs. There is thus no Gold Standard drugs or algorithm to manage post craniotomy pain and this review aims to discuss the common availability of medicine and review the various options available for successful management of post craniotomy pain (PCP). Each neurosurgical centre must have a protocol and guidelines regarding PCP management which will be easier for the juniors and nurses to follow. Multimodality treatment can achieve best results and further controlled trials with the different medications alone or in combination, studies in cannabinoid derivatives in future can help to formulate and ideal PCP management algorithm.